2017
DOI: 10.1021/acs.bioconjchem.7b00562
|View full text |Cite
|
Sign up to set email alerts
|

Improved Photoinduced Fluorogenic Alkene–Tetrazole Reaction for Protein Labeling

Abstract: The 1,3-dipolar cycloaddition reaction between an alkene and a tetrazole represents one elegant and rare example of fluorophore-forming bioorthogonal chemistry. This is an attractive reaction for imaging applications in live cells that requires less intensive washing steps and/or needs spatiotemporal resolutions. In the present work, as an effort to improve the fluorogenic property of the alkene-tetrazole reaction, an aromatic alkene (styrene) was investigated as the dipolarophile. Over 30-fold improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…[96] More recently,t etrazole compounds have been developed by Qing Lin and co-workers in the context of protein functionalisation using ap hotoactivated 1,3-dipolar cycloaddition process (Scheme10). [97][98][99][100][101][102] The reaction was claimed to be bio-orthogonal, [101,103] and was given the name "photo-click". However, detailed mechanistic studies from two groups have independently refuted this claim and have shown that the ni-Scheme9.Photoexcitation of aryl azirinesa nd subsequent 1,3-dipolar addition reactions of the nitrile imine intermediate with unsaturated alkenes.…”
Section: Dipolar] Cycloadditionsmentioning
confidence: 99%
“…[96] More recently,t etrazole compounds have been developed by Qing Lin and co-workers in the context of protein functionalisation using ap hotoactivated 1,3-dipolar cycloaddition process (Scheme10). [97][98][99][100][101][102] The reaction was claimed to be bio-orthogonal, [101,103] and was given the name "photo-click". However, detailed mechanistic studies from two groups have independently refuted this claim and have shown that the ni-Scheme9.Photoexcitation of aryl azirinesa nd subsequent 1,3-dipolar addition reactions of the nitrile imine intermediate with unsaturated alkenes.…”
Section: Dipolar] Cycloadditionsmentioning
confidence: 99%
“…While both PAL- and FDC1- enzymatic reaction steps are performed in aqueous medium, styrene 3 and tetrazole 4 are poorly water-soluble and also triaryl-pyrazolines 5 provide higher fluorescence signal turn-on in neat organic solvents 47 . However, their successful use for in vivo/in vitro protein labeling in phosphate-buffer/acetonitrile 1:1 ( v / v ) has also been reported 49 , 54 . Accordingly, to test which solvent system provides more efficient fluorescence detection, we performed the FDC1-mediated decarboxylation of cinnamic acid 2 in phosphate-buffer , followed by addition of equal volumes of organic solvents, with various polarities, as the water-miscible acetonitrile or methanol favoring the solubilization of styrene in the reaction mixture, but also n -hexane promoting the extraction of styrene.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the sequential use of PAL and FDC1 reactions in genetically engineered whole cells was also demonstrated within the biosynthesis of styrene, 1,2-ethanediols or other valuable products 44 46 . The 1,3-dipolar cycloaddition reaction between an alkene and a tetrazole represents an attractive method of fluorophore-forming bioorthogonal chemistry, with various diaryltetrazoles shown to be highly sensitive fluoroprobes for the detection of alkenes 47 49 .
Figure 2 The fluorescent coupled-enzyme assay for PAL-activity assessments.
…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work used genetically encoded artificial amino acids bearing alkenes [6] and cyclopropenes [7] for site‐specific, photo‐induced labelling of pre‐modified proteins in vitro and in vivo. One of the attractive features of tetrazole‐alkene photochemistry is that reactivity can be modified to increase coupling rates via structural and frontier orbital control on the tetrazole [8–11] or the alkene partners [12, 13] . However, a drawback of tetrazole photochemistry is the need to use short wavelength light (≈302 nm) to form the nitrile imine which is potentially damaging to proteins like mAbs [14, 15] …”
Section: Figurementioning
confidence: 99%
“…One of the attractive features of tetrazole-alkene photochemistry is that reactivity can be modified to increasec oupling rates via structurala nd frontier orbitalc ontrol on the tetrazole [8][9][10][11] or the alkene partners. [12,13] However,adrawbacko ft etrazole photochemistry is the need to use short wavelength light ( % 302 nm) to form the nitrile imine which is potentially damaging to proteins like mAbs. [14,15] The photo-click reaction betweent etrazoles and alkenes was reported to be bioorthogonal.…”
mentioning
confidence: 99%